INTEGRATED REPORTING: DOES IT IMPROVE THE QUALITY OF ESG REPORTING OR MERELY SYMBOLIZE A COMMITMENT TO SUSTAINABILITY? - Tania Haura Azahra; Yusnaini Yusnaini (PT. Media Akademik Publisher, 2026)
The increasing global pressure on Environmental, Social, and Governance (ESG) practices has encouraged companies to adopt Integrated Reporting (IR) as a comprehensive reporting approach that combines financial and non financial information. IR is often promoted as a tool to enhance transparency and accountability in ESG reporting; however, its actual effectiveness remains debated in academic literature. This study aims to systematically evaluate whether IR genuinely improves the quality of ESG reporting or merely acts as a symbolic representation of sustainability commitment. The research employs a Systematic Literature Review (SLR) method, analyzing articles published between 2021 and 2026 from reputable national and international journals indexed in Scopus, Sinta, Garuda, and Google Scholar. A total of 25 selected articles were examined using thematic analysis. The findings indicate that most studies report improvements in ESG disclosure quality, particularly in terms of materiality, information connectivity, and transparency regarding sustainability risks. Nevertheless, several studies highlight the persistence of symbolic and legitimacy driven practices, especially in regions with weaker regulatory frameworks. Furthermore, the effectiveness of IR is found to depend significantly on the strength of corporate governance and regulatory pressure. This study contributes to the development of IR–ESG literature and offers practical implications for regulators and investors.